Hyperspectral data in water stress detection - Riczu, P.; Nagy, A.; Tamás, J. (International Journal of Horticultural Science, 2014)
Remote sensing methods are applied widespread to investigate large land fields. Within these methods the status of certain vegetation can be determined based on the reflectance spectra of the chlorophyll, in order to support agriculture, forestry and the evaluation of soil pollution. The main aims of our study were to determine and validate the reflectance spectra of fruit tree species, in order to facilitate the identification and evaluation of stressed fruit trees in orchards.